Distributed computing : 30th International Symposium, DISC 2016, Paris, France, September 27-29, 2016. Proceedings /: 30th International Symposium, DISC 2016, Paris, France, September 27-29, 2016. Proceedings. (2016) - Unknown
No abstract available